Indonesian - English Code Mixing In Supernova 4 Partikel Novel (2012) Written By Dee - Hidayati, Nur; , Drs. Maryadi M. A.; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This research investigates code mixing in Supernova 4 "Partikel" Novel (2012) Written by Dee. The study aims to describe 1) the types of code mixing and 2) the reasons of using code mixing in Supernova 4 Partikel Novel (2012) written by Dee. This research applies descriptive qualitative method. The data of this research are Indonesian - English code mixing occurred in Supernova 4 Partikel Novel (2012) and the information of the reasons of using code mixing. The data are taken from Supernova 4 Partikel Novel (2012) written by Dee. The way to collect data is documentation method. The results show that there are 77 data or 62, 1% belong to insertion, 42 data or 33, 87% belong to alternation, and 5 data or 4, 03% belong to congruent lexicalization. On the category insertion, there are 2 types of insertion such as 70 data belong to insertion of word, 3 data belong to insertion of hybrid, 2 data belong to insertion of word repetition, 2 data belong to insertion of phrases. The second finding is dealing with the reasons of code mixing. The result shows that there are 19 data or 15, 32% belong to need filling motive, and 105 data or 84, 68% belong to prestige filling motive. The analyzing data of the types code mixing by using Muysken's theory and the reasons of mixing code by using Hockett's theory.